Feeding MGA to grazing heifers - L. Corah; F. Brazle; Jeffrey L. Davidson (Kansas Agricultural Experiment Station Research Reports, 1981)
Feeding MGA to grazing heifers suppressed estrus but did not improve gain.
Keywords: Cattlemen& #x27; s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; MGA; Heifers